Fabrication and Evaluation of Porous Beta-Tricalcium Phosphate/Hydroxyapatite (60/40) Composite as a Bone Graft Extender Using Rat Calvarial Bone Defect Model. (17th December 2013) - Lee, Jae Hyup; Ryu, Mi Young; Baek, Hae-Ri; Lee, Kyung Mee; Seo, Jun-Hyuk; Lee, Hyun-Kyung
Abstract : Beta-tricalcium phosphate ( β -TCP) and hydroxyapatite (HA) are widely used as bone graft extenders due to their osteoconductivity and high bioactivity. This study aims to evaluate the possibility of using porous substrate with composite ceramics ( β -TCP: HA = 60% : 40%, 60TCP40HA) as a bone graft extender and comparing it with Bio-Oss. Interconnectivity and macroporosity of β -TCP porous substrate were 99.9% and 83%, respectively, and the macro-porosity of packed granule after crushing was 69%. Calvarial defect model with 8 mm diameter was generated with male Sprague-Dawley rats and 60TCP40HA was implanted. Bio-Oss was implanted for a control group and micro-CT and histology were performed at 4 and 8 weeks after implantation. The 60TCP40HA group showed better new bone formation than the Bio-Oss group and the bone formation at central area of bone defect was increased at 8 weeks in micro-CT and histology. The percent bone volume and trabecular number of the 60TCP40HA group were significantly higher than those of Bio-Oss group. This study confirms the usefulness of the porous 60TCP40HA composite as a bone graft extender by showing increased new bone formation in the calvarial defect model and improved bone formation both quantitatively and qualitatively when compared to Bio-Oss.